Embedding soft skills to the teacher education undergraduate curriculum: perceptions of faculty and students - Vithanapathirana, M.V. (My University, 2018)
Soft skills have become a subject of increasing interest. Soft skills acquisition enhances personality development resulting in success in professional and personal life. Emphasis on the soft skills development in higher education has been a major focus in all undergraduate programs. The objective of the study was to conduct a status study on the implementation of soft skills development in the Bachelor of Education (BEd) program of the Faculty of Education, University of Colombo, Sri Lanka which is the oldest and the highly recognized BEd program of the country. Within the case study purposive samples of ten faculty members and thirty students were selected. Data were collected on student perceptions, faculty perceptions and self reflections of the researcher who was the coordinator of the soft skills program. Data collection strategies were focus group interviews and reflective notes. Findings reveal that the students preferred soft skills workshops conducted as stand-alone support activities. Their participation in classroom activities with soft skills components was also encouraging. Faculty members were in favour of embedding soft skills to the teacher education curricula. The study suggests that a wide range of soft skills to be embedded into all teacher professional development programs through innovative activities.
Keywords: Soft Skills, Teacher Education, Higher Education, Embedded Curriculum